PENINGKATAN PENGETAHUAN ORANG TUA DALAM PERAWATAN EFEK SAMPING KEMOTERAPI PADA ANAK LEUKEMIA MELALUI BOOKLET DI RUMAH SAKIT - Happy Indri Hapsari (LPPMK STIKES Widyagama Husada, 2019)
Leukemia is the number one cancer that attacks children aged 0 to 18 years. Parents who have children with leukemia will experience a heavy burden in caring for children. Health education is one way for nurses to ease the burden of parents in finding information about leukemia. The use of booklets has long been known as a medium in health education, where effectiveness is very significant in increasing parental knowledge. The purpose of the study: to determine the effect of health education with booklets on the level of knowledge of parents in caring for leukemic children who are on chemotherapy. Method: quasi experiment and using Wilcoxon data analysis. Results: p-value 0.00, where the p - value <0.005 so that there is an effect of booklets in increasing parental knowledge about the treatment of side effects of chemotherapy in children with leukemia. Conclusion: booklet administration increases parental knowledge about the treatment of chemotherapy side effects in leukemic children.